2016
DOI: 10.1177/0148607116633800
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Hospitalized Children With a Diagnosis of Malnutrition

Abstract: Hospitalized children with a CDM are associated with more comorbidities, longer hospital stay, and higher healthcare costs than those without this diagnosis. These undernourished children may utilize more healthcare resources in the hospital and community. Clinicians and policymakers should factor this into healthcare resource utilization planning. Recognizing and accurately coding malnutrition in hospitalized children may reveal the true prevalence of malnutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 43 publications
(52 reference statements)
0
47
0
7
Order By: Relevance
“…In the past, the lack of a uniform definition of pediatric malnutrition that addressed it in both developing and developed countries resulted in widely varying prevalence rates (6%–51%) and heterogeneous nutrition screening practices 1 . While it is well known that malnutrition results in poorer clinical outcomes (eg, immune dysfunction, poor wound healing, developmental delay) and increased hospital costs (eg, prolonged hospital stay, increased use of nutrition support), identifying pediatric malnutrition remained elusive 2 5 …”
Section: Consensus Statement Primary Indicators Of Pediatric Malnutrimentioning
confidence: 99%
See 2 more Smart Citations
“…In the past, the lack of a uniform definition of pediatric malnutrition that addressed it in both developing and developed countries resulted in widely varying prevalence rates (6%–51%) and heterogeneous nutrition screening practices 1 . While it is well known that malnutrition results in poorer clinical outcomes (eg, immune dysfunction, poor wound healing, developmental delay) and increased hospital costs (eg, prolonged hospital stay, increased use of nutrition support), identifying pediatric malnutrition remained elusive 2 5 …”
Section: Consensus Statement Primary Indicators Of Pediatric Malnutrimentioning
confidence: 99%
“…Consequently, malnutrition codes may affect reimbursement, whereas FTT codes may not. Diagnosing the severity of pediatric malnutrition with uniform cutoffs in children with FTT will allow for the appropriate allocation of resources, resulting in the correct level of reimbursement 1 , 2 . By using the malnutrition‐specific codes in malnourished children with FTT, providers and researchers will be able to determine which interventions result in improvement in the severity of malnutrition.…”
Section: Paradigm Shiftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Malnutrition has been demonstrated to significantly hinder the recovery of pediatric patients with chronic or acute illness. In a recent nationwide study, hospitalized pediatric patients who had a malnutrition diagnosis code were found to have more comorbidities such as fluid and electrolyte disorders, deficiency anemia, and peripheral vascular disease as well as a longer hospital stay and greater hospital costs than those without the diagnosis . There has been discrepancy in previous literature on the prevalence of malnutrition among hospitalized pediatric patients, ranging from 6%–51% .…”
Section: Introductionmentioning
confidence: 97%
“…In developed countries, malnutrition is predominantly related to disease . Hospitalized undernourished children have increased comorbidities, longer hospital stays, higher hospital costs, and greater likelihood of requiring continued medical care after discharge . Despite this, malnutrition has not drawn the appropriate attention or resources for intervention because of underreporting and assumptions that it is an inevitable consequence of underlying disease .…”
mentioning
confidence: 99%